2023
DOI: 10.48550/arxiv.2301.12133
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The first variation of the matter energy-momentum tensor with respect to the metric, and its implications on modified gravity theories

Abstract: The first order variation of the matter energy-momentum tensor Tµν with respect to the metric tensor g αβ plays an important role in modified gravity theories with geometry-matter coupling, and in particular in the f (R, T ) modified gravity theory. We obtain the expression of the variation δTµν/δg αβ for the baryonic matter described by an equation given in a parametric form, with the basic thermodynamic variables represented by the particle number density, and by the specific entropy, respectively. The first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…In line with the standard cosmological model, we consider DM as a perfect, pressureless fluid, with T µν DM = ρ u µ u ν and T DM = −ρ. In this case [41] have shown that, in standard astrophysical and cosmological settings, where the entropy and particle production rates remain unchanged during the dynamical evolution of the fluid, the variation of the trace of the stress energy tensor can be written in a closed form as…”
Section: Relativistic Action and Equations Of Motionmentioning
confidence: 99%
“…In line with the standard cosmological model, we consider DM as a perfect, pressureless fluid, with T µν DM = ρ u µ u ν and T DM = −ρ. In this case [41] have shown that, in standard astrophysical and cosmological settings, where the entropy and particle production rates remain unchanged during the dynamical evolution of the fluid, the variation of the trace of the stress energy tensor can be written in a closed form as…”
Section: Relativistic Action and Equations Of Motionmentioning
confidence: 99%
“…To find modified field equation one only needs to derive last term in action (21). In this context, the last term in action (21) given by [29] δT δg μν = T μν + T μν (22) in which T μν defined by…”
Section: Covariant Thermodynamics and New Gravity Modelmentioning
confidence: 99%